2015
DOI: 10.3109/17453674.2015.1033309
|View full text |Cite
|
Sign up to set email alerts
|

Which patients do not recover from shoulder impingement syndrome, either with operative treatment or with nonoperative treatment?

Abstract: Background and purpose — Shoulder impingement syndrome is common, but treatment is controversial. Arthroscopic acromioplasty is popular even though its efficacy is unknown. In this study, we analyzed stage-II shoulder impingement patients in subgroups to identify those who would benefit from the operation.Patients and methods — In a previous randomized study, 140 patients were either treated with a supervised exercise program or with arthroscopic acromioplasty followed by a similar exercise program. The patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…[9,10] In the literature, it was reported that AC joint injection should be ultrasound-guided as in the GH joint since the accuracy rate in blind injections is 40-72%. [11][12][13][14][15] Resection can be performed with a direct view of the joint space with open DCR; however, AC joint instability and persistent pain associated with poor functional outcome can occur due to damage in deltoid fascia, superior AC ligament, and capsule. [16,17] Better results can be achieved by preserving these structures with arthroscopic DCR.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] In the literature, it was reported that AC joint injection should be ultrasound-guided as in the GH joint since the accuracy rate in blind injections is 40-72%. [11][12][13][14][15] Resection can be performed with a direct view of the joint space with open DCR; however, AC joint instability and persistent pain associated with poor functional outcome can occur due to damage in deltoid fascia, superior AC ligament, and capsule. [16,17] Better results can be achieved by preserving these structures with arthroscopic DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up periods in future trials need to be longer to learn more about the course of SIS. 63 In our meta-analysis 137 studies assessed patients within 2 weeks after end of treatment, 54 studies at 6 weeks, 52 studies at the end of 3 months, 24 studies up to 6 months, whereas only 21 studies had a follow-up longer than 6 months, and in 3 studies the length of follow-up was unclear. 51 64 65 Not all interventions were compared against validated sham interventions or placebo.…”
Section: Strength and Limitations Of This Reviewmentioning
confidence: 98%
“…A similar FIMPACT study 4 conducted by Paavola et al yielded the same conclusion. Ketola et al conducted a study [24][25][26][27][28] to compare arthroscopic acromioplasty with conservative treatment for shoulder impingement and the follow-up time lasted for more than 10 years, the results revealed that there were no significant differences in the changes of the rotator cuff between the two groups at the five-year follow-up, and they also conducted a detailed subgroup analysis, while no significant difference was found in the subgroup analysis either. The study 21 conducted by Rahme et al compared open surgery with conservative treatment for shoulder impingement, and the results showed that open surgery achieved better clinical results than conservative treatment, and they believed that shoulder impingement was caused by subacromial capsular compression, which was in conflict with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…By carefully reading the full text, it was found that: 3 articles 16-18 were just study protocol, 1 article 6 we couldn't extract the data we need, 2 article 19,20 were not randomized controlled trial, 3 articles [21][22][23] were based on the comparison of other surgical method and conservative management. 11 studies met our inclusion and exclusion criteria, and among these studies, 5 studies [24][25][26][27][28] published by Ketola et al described the same clinical study and the follow-up time of these studies all belonged to our long-term subgroup, so we only included as one. 7 eligible RCTs 4,5,28-32 were included eventually in our meta-analysis.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%